Estratégias e desafios do atendimento psicoterápico com crianças institucionalizadas: um estudo a partir da teoria de D.W. Winnicott - Ponce, Larissa Garcia (2018)
This study aimed to investigate, through clinical case studies, the strategies and challenges found in the psychotherapeutic care of five children sheltered in an Institutional Shelter in a country town of São Paulo State. The reports of these sessions were analyzed based on psychoanalysis, with a greater emphasis on the contributions of D. Winnicott. Two aspects were examined with special attention: the established clinical management and the evolution of psychotherapy in each history. The instruments used to find and read these data were: life and sheltering history of the patients/participants, presented in the registration form of the institution, and clinical material from playful psychotherapy. In four of the five cases, the time of psychotherapy was short (five to ten sessions), due to an abrupt interruption of the psychotherapeutic processes. In the only case with a longer duration (thirty sessions), there was the possibility of a therapeutic withdrawal performed progressively. Regarding the treatment results, one patient did not show significant achievements; the others demonstrated benefits from the psychotherapeutic process and exhibited improvement in symptoms or thawing of emotional maturation. The role of each action of differentiated clinical management in the setting was listed and some of them served as coping strategies of some of the challenges that were interposed. In addition to these actions, the importance of the management promoted by the social environment to shelters was evidenced. In order for this to be guaranteed, both the sheltering institution and the Judiciary are expected to commit themselves to protect children from future trauma, especially those which could be avoided by a more judicious and realistic analysis of the family circumstances in each case. Finally, it was pointed out the need to implement psychotherapy services in Shelters throughout the country, as well as psychological care programs for those who return home after sheltering. This proposition is corroborated by the obvious importance of a listening, receiving and psychological support space for the recovery of personal maturation of deeply traumatized people, as postulated byWinnicott, in addition to actively collaborating in the construction of a healthy society and, therefore, more prepared to care for their children and adolescents